Hubungan Gaya Kepemimpinan Transformasional dan Gaya Kepemimpinan Transaksional Dengan Kualitas Pelayanan Kasus Hotel Mulia Senayan Jakarta - Netty Evy Glorya Manurung; Izaak Samuel Leihutu (CERED Indonesia Institute, 2020)
Tourism industry development is very fast and creating a competitiveness among the industry, whether nationally and globally. To win the competition they have to be creative to win the guest’s heart by creating the service quality that been expected by the customers or even beyond their expectation. In order to achieve the service quality as mentioned above, leaders will take their roles to drive all the instruments of service quality to be performed by the employee in maximum capacity. Leader’s influences affected to service quality given by the employee to customers. Leadership topic is always a very interesting topic to be discussed and yet hard to be understood and implemented. In this modern era there are two leadership styles which been acknowledge by the former researcher, they are Transformational Leadership and Transactional Leadership. Few studies had been done and concluded that transformational leadership needed to ensure the service quality achieved by the operations. Hotel Mulia Senayan Jakarta is one of the biggest hospitality industry in Indonesia which provides accomodations and it is very important for them to ensure the service quality given to guests are achieved from the roles performed by the hotel leaders.